Thinking about schools a foundations of education reader - Hilty, Eleanor Blair. (Westview Press, 2011)
"Designed specifically for students with little or no education background, Thinking About Schools is an essential collection of classic and contemporary readings that provides a complete, balanced overview of educational foundations. Anchored in classic scholarship from the 1960s to today, this book also incorporates a number of thought-provoking popular essays that will engage students and encourage critical thinking about vital issues concerning the purpose of education, curriculum content, the roles and responsibilities of students and teachers, and new directions for education in the twenty-first century. In addition to selecting each reading for its impact and accessibility, editor Eleanor Blair Hilty further promotes student comprehension by including introductions, discussion questions, guides to further reading, and related resources for each of the five parts"--